2009
DOI: 10.1373/clinchem.2008.115899
|View full text |Cite
|
Sign up to set email alerts
|

National Academy of Clinical Biochemistry Laboratory Medicine Practice Guidelines: Emerging Biomarkers for Primary Prevention of Cardiovascular Disease

Abstract: BACKGROUND:Heart disease and stroke continue to be the leading causes of death in the US. As a result, investigators continue to look for new and emerging biomarkers of disease risk. Because many of these emerging biomarkers are not as well documented as those of conventional lipid and lipoprotein risk factors, their value in clinical practice needs to be critically appraised and appropriate guidelines developed for their proposed use.CONTENT: The National Academy of Clinical Biochemistry (NACB) convened a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(111 citation statements)
references
References 3 publications
2
105
0
4
Order By: Relevance
“…Elevated hsCRP level has been consistently associated with cardiovascular disease and thus is recommended for risk assessment in patients with intermediate risk according to guidelines. [19][20][21] However, previous researches on the association between hsCRP and first stroke yielded conflicting results. 12,22,23 A large meta-analysis with a hsCRP values were divided into 3 levels (low risk, <1.0 mg/L; average risk, 1-3 mg/L; and high risk, >3 mg/L) by recommendation from the Centers for Disease Control and American Heart Association for primary prevention of cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated hsCRP level has been consistently associated with cardiovascular disease and thus is recommended for risk assessment in patients with intermediate risk according to guidelines. [19][20][21] However, previous researches on the association between hsCRP and first stroke yielded conflicting results. 12,22,23 A large meta-analysis with a hsCRP values were divided into 3 levels (low risk, <1.0 mg/L; average risk, 1-3 mg/L; and high risk, >3 mg/L) by recommendation from the Centers for Disease Control and American Heart Association for primary prevention of cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although HDL-C has protective effects for atherosclerosis development, this may not break down the inflammatory period. Clinical studies have showed that the risk of cardiovascular disease, myocardial infarctus, stroke, angina pectoris increased with high serum cystatin C concentrations [15,16]. Serum cystatin C concentrations of CAD group was higher than control group but this association was not statistically significant.…”
Section: Discussionmentioning
confidence: 89%
“…The increase in the concentrations of BNP or NT-pro-BNP is associated with higher mortality in the following 2-7 years in the studied populations. However, the benefits of therapy based on these assessments are uncertain (25) .…”
Section: Bnp In the Assessment Of Cardiac Functionmentioning
confidence: 99%